State level agreed-upon factors contributing more effective policymaking for public sector services for effective local-level work with NEETs - Paabort, Heidi; Beilmann, Mai (Calitatea Vieții, 2021)
Supporting young people who are not in education, employment or training (NEET) represents a new global policy challenge. There is a need to increase knowledge about policymaking connected to multidisciplinary approaches in order to provide better services for NEET youth. This study focuses on interpretations by specialists in the youth field in Estonia regarding the current public policy support system for NEETs and the associated factors affecting the achievement of policy goals. Based on document analysis and semi-structured interviews with specialists from all levels of the national NEET support system, this study demonstrates that the cross-sectoral and multi-level public policy system for NEETs lacks sufficient understanding of the central aims. The support strategy is, rather, created for use within a single structure and does not have a common meaning from a system-wide perspective. State-level coordinating parties need a common understanding at the beginning of policy creation concerning the system’s long-term aims, information flow and performance, agreed-upon roles transcending sectors, and process management across structures. This change would enable better outreach and integrated services at the local level and be accurately based on the needs of youth with heterogeneous backgrounds whilst avoiding barriers at the individual case level.